Early Clinical Experiences of Esketamine Nasal Spray in the UK in Adults with Treatment-Resistant Major Depressive Disorder: Advisory Panel Recommendations - Young AH; Abdelghani M; Juruena MF; Nikolova VL; Nilforooshan R (Neuropsychiatric Disease and Treatment, 2023)
Allan H Young,1 Mohamed Abdelghani,2 Mario F Juruena,1,3 Viktoriya L Nikolova,1 Ramin Nilforooshan4,5 1Institute of Psychiatry, Psychology and Neuroscience, King’s College London, London, UK; 2Camden and Islington NHS Foundation Trust, London, UK; 3Maudsley Advanced Treatment Service (MATS), South London and Maudsley NHS Foundation Trust, London, UK; 4Surrey and Borders Partnership NHS Foundation Trust, Leatherhead, UK; 5Faculty of Health and Medical Sciences, University of Surrey, Guildford, UKCorrespondence: Allan H Young, Institute of Psychiatry, Psychology and Neuroscience, King’s College London, PO72, 16 De Crespigny Park, Denmark Hill, London, SE5 8AF, UK, Tel +44 207 848 0088, Email allan.young@kcl.ac.ukPurpose: Treatment-resistant depression (TRD) is associated with profound morbidity for patients, placing a significant burden on those affected, the health service and wider society. Despite this, TRD remains chronically underserved in terms of viable treatment options. To address this gap, an advisory panel of psychiatrists and clinical researchers with experience in managing TRD convened to develop best practice statements on the use of esketamine nasal spray, one of the first TRD treatments to be licensed in 30 years.Methods: During a virtual meeting held on 12th November 2020, the advisory panel shared their experiences of using esketamine nasal spray in their clinical practice. The meeting focused on developing and refining recommendations for setting up and running an efficient esketamine nasal spray clinic for patients living with TRD. At the conclusion of the meeting, agreement was reached on all recommendation statements.Results: In setting up an esketamine nasal spray clinic, it is important to consider the logistical requirements involved and put measures in place to ensure it runs as efficiently as possible. Educating patients about the treatment and maintaining their well-being is paramount for preventing discontinuation. Putting in place checklists can be a useful strategy for ensuring treatment appointments run smoothly and safely.Conclusion: Providing additional treatment options for the management of TRD, such as esketamine nasal spray, is likely to be key to improving the long-term outcomes of this underserved patient population.Keywords: depression, TRD, MDD, antidepressant, glutamate